(untitled) (International Journal of Management and Sustainability, 2018)
The modeling, simulation and analysis of the energy conversion equations describing the behavior of a hybrid system PV and wind turbine, and hybrid system for electrical power generation are presented. A numerical model based on the aforementioned equations was developed, coded and results were presented, discussed compared to experimental data reported in the literature. The model is intended for optimization and as design tool for such hybrid systems. The model predicted results compared fairly to experimental data under various conditions. A stability analysis was also performed by the mathematical modeling for the hybrid system. It is important to point out that this analysis has been carried out so that in the near future one of these power generation systems to be exploited to a great extent in the locality of Quingeo-Puntahacienda.